Bibliometric Analysis of Halal Tourism (Hajj and Umrah) Development in the World - Jumali, Endang; Fitriyani, Fitriyani (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This research highlights the theoretical basis and future research directions in religious tourism and related topics from 2003 to 2023. 1,689 documents from the Scopus database related to religious tourism and the Umrah Hajj have been analyzed using VOS viewer software. This analysis found that research on religious tourism and the Umrah pilgrimage experienced a consistent increase. The most influential countries in the research were Saudi Arabia, Indonesia, Malaysia, France, and Australia. Studies on Umrah mass gathering, respiratory viruses, preventive measures, and pilgrimage season in Hajj and Umrah religious tourism are predicted to be a significant research focus, as can be seen through keyword co-occurrence analysis. The results of this study provide a comprehensive evaluation of the religious tourism literature over a decade using bibliometric and network analysis. The results of this research can help researchers gain a deeper understanding of the study of religious tourism as a whole and determine priorities for future research.